Rural tourism development and poverty alleviation : Sabaragamuwa province in Sri Lanka - K.M.L.M. Manjula Gunarathna (2015)
This study examined rural tourism development and poverty alleviation: Sabaragamuwa province in Sri Lanka. It employed mixed method approach. Secondary data were gathered from reputable institutions including Sri Lanka Tourism Development Authority, Central Bank of Sri Lanka, Department of Census and Statistics in Sri Lanka since 1977. Primary data were collected from field survey of Sabaragamuwa province in Sri Lanka using observations, questionnaires and interviews. Primary data represented qualitative and quantitative. Simultaneous and sequential mixing methods were used to integrate both types of data. Based on the cumulative and cyclical inter-dependence theory and literature review, dependent and independent variables were recognized. In that, six hypotheses were tested. The study was designed on a research problem reviewing two main postulations that (1) prevalence of poverty can be alleviated via rural tourism development in Sri Lanka and; (2) rural tourism can be developed in Sri Lanka in its existing tourism system. In that, the study scrutinized the existing relationship between tourism development and poverty alleviation, key factors, existing obstacles and specific determinates regarding rural tourism development and poverty alleviation in Sri Lanka as reflected in its specific objectives and subresearch questions. The study found two main reasons for lack of correlation between rural tourism development and poverty alleviation in Sabaragamuwa, Sri Lanka. They are (1) shortage of available rural resources utilisation and (2) lack of rural community participation. It is also found that, seasonality, war effects, barriers, lack of combing programme had caused above mentioned relationship. The study concluded that existing tourism system in Sri Lanka links with a deficiency of community based approach (DCBA). Also, the study found that there is a significant relationship between community and assets. It means that lack of community participation had resulted in the lack of resources utilisation. The study opined that ABCD model makes a useful path between rural tourism development poverty alleviation in Sri Lanka. The findings, conclusions and suggestions exhort policy makers, researchers and community to make a platform for the advocacy of rural tourism as a viable instrument of poverty alleviation in Sri Lanka. It is important to highlight the role of rural tourism as an economic activity that is capable of alleviating poverty and stimulate the economy of Sri Lanka.